Autosomal dominant palmoplantar hyperkeratosis and sensorineural deafness in three generations. Issue 1 (January 1992) - Sharland, M; Bleach, N R; Goberdhan, P D; Patton, M A
Abstract : A family is presented with autosomal dominant progressive palmoplantar hyperkeratosis, which is invariably associated with a slowly progressive, bilateral, high frequency, sensorineural hearing loss. The family show no other ectodermal abnormality. The differential diagnosis and possible mechanisms are discussed. This family appears to represent a unique variant in the hyperkeratosis-deafness association.